Imported scrub typhus in Europe: Report of three cases and a literature review. Issue 42 (July 2021) - Costa, Cecilia; Ferrari, Anna; Binazzi, Raffaella; Beltrame, Anna; Tacconi, Danilo; Moro, Lucia; Edouard, Sophie; Parola, Philippe; Buonfrate, Dora; Gobbi, Federico
Abstract: Background: Scrub typhus is a vector-borne rickettsial infection, which can cause relevant morbidity and mortality. While the number of cases is around a million per year globally, the infection is seldom diagnosed in travellers from Europe. Methods: We herein report three cases diagnosed in Italian travellers and review the literature about imported cases in Europe in the last 60 years. Results: Three participants to the same hiking trip to the forest of northern Laos presented fever and other symptoms, including eschars (2 individuals) and skin rash (2 individuals). Overall, they didn't report complications, and recovered soon after doxycycline treatment. Diagnosis was retrospectively confirmed with PCR in one of them. The review collected data from 40 patients. Almost all of them (95%) presented fever, more than a half had headache, skin rash, eschars, arthromyalgias. 73% of them were hospitalized, and 16.2% needed intensive care. Diagnosis was confirmed by serology in almost all cases (94.6%). Most patients (88%) were treated with doxycycline. All patients survived, although one case resulted in incomplete tetraparesis. Conclusions: Scrub typhus should be considered in all travellers coming back from endemic areas and presenting with acute febrile illness. Laboratory diagnosis can be challenging, as specific tests are not widely available. In case of clinical suspicion, a prompt treatment with oral doxycycline could avoid severe complications.